2019
DOI: 10.1200/jco.2019.37.4_suppl.187
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dabrafenib (D) and trametinib (T) in patients (pts) with BRAF V600E–mutated biliary tract cancer (BTC): A cohort of the ROAR basket trial.

Abstract: 187 Background: BTCs are rare, aggressive malignancies with poor prognoses. Treatment options and outcomes after first-line therapy are not well defined. Median progression-free survival (PFS) in second-line BTC is < 5 mo. Combined BRAF + MEK inhibition is efficacious in BRAF V600–mutated anaplastic thyroid cancer, melanoma, and lung cancer, but less so in BRAF V600E-mutated colorectal cancer. Activating BRAF V600E mutations have been reported in 0% to 20% of BTCs; thus, D (BRAF inhibitor) + T (MEK inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 0 publications
2
52
0
2
Order By: Relevance
“…The first reports with the combination of dabrafenib (BRAF inhibitor) plus trametinib (MEK inhibitor) was presented by Wainberg et al, reporting outcomes from the biliary tract cohort of the phase II ROAR basket trial. The data revealed a 41% response rate in BRAFV600E mutated biliary tract cancers treated with dabrafenib and trametinib and stable disease as best response in another 45% of patients 17. The median progression-free survival in this study was 9.2 months and median overall survival was 11.7 months, which is comparable to outcomes with standard of care first-line chemotherapy.…”
supporting
confidence: 61%
“…The first reports with the combination of dabrafenib (BRAF inhibitor) plus trametinib (MEK inhibitor) was presented by Wainberg et al, reporting outcomes from the biliary tract cohort of the phase II ROAR basket trial. The data revealed a 41% response rate in BRAFV600E mutated biliary tract cancers treated with dabrafenib and trametinib and stable disease as best response in another 45% of patients 17. The median progression-free survival in this study was 9.2 months and median overall survival was 11.7 months, which is comparable to outcomes with standard of care first-line chemotherapy.…”
supporting
confidence: 61%
“…In a basket trial of rare tumours, including CCA harbouring RAF V600E mutations, the BRAF inhibitor dabrafenib and the MEK inhibitor trametinib resulted in a response rate of 42% per investigator assessment in 35 patients with CCA. 41 The median PFS by investigator assessment was 9.2 months, and the median OS was 11.7 months in this cohort. Mutations in the following genes have been identified but have proven difficult to target: PRKACA, PRKACB, ELF3, ARID1A, ARID1B and BAP1.…”
Section: Fgfr Inhibitorsmentioning
confidence: 66%
“…In two independent reports, the combination of Dabrafenib and Trametinib showed durable clinical responses [55,56]. Finally, the preliminary results of a basket trial involving patients with BRAF mutation showed, in a cohort of pretreated biliary tract cancer, a response rate of 42% with a median overall survival of 11.7 months [57].…”
Section: Mapk (Mitogen-activated Protein Kinases) Pathwaymentioning
confidence: 94%